UJI KUAT TEKAN DAN KUAT TARIK BELAH PADA BETON DENGAN SERAT KAWAT NYAMUK PADA MUTU FC’ = 19,3 MPA - Handika Setya Wijaya; Adrianus Tandi (Prokons: Jurnal Teknik Sipil, 2020)
Concrete is one of the construction materials that is currently widely used by the community to build buildings. This is evidenced by the large number of construction of buildings, roads, irrigation channels and other construction. Until now, Indonesian people still use a little concrete. The problem that we want to know is how the effect of adding mosquito wire fiber to compressive strength, tensile strength and elastic modulus of concrete using concrete quality fc '= 19.3 MPa. The purpose of this study is to add additional mosquito wire fiber can be used as an added component of concrete components that have high strength and good quality but are economically valuable for compressive strength, tensile strength and elastic modulus. The method used is secondary and primary data. The results of this study are compressive strength 0% = 15,839 MPa, 1% = 13,657 MPa, 3% = 10,137 MPa, 5% = 9,173 MPa, tensile strength 0% = 7,392 MPa, 1% = 8,205 MPa, 3% = 8,504 MPa, 5% = 9,038 MPa. and elastic modulus 0% = 29131,385 N / mm2, 1% = 14575.68 N / mm2, 3% = 10303,133 N / mm2, 5% = 7030,893 N / mm2. The results of this study found that the addition of mosquito wire fiber can reduce the compressive strength of concrete and modulus. While the tensile strength and modulus of elasticity increase. So that the mosquito wire is not suitable for concrete compressive strength and elastic modulus.